2021
DOI: 10.1002/jsfa.11333
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a thermostable cellobiose 2‐epimerase from Caldicellulosiruptor sp. Rt8.B8 and production of epilactose using Bacillus subtilis

Abstract: BACKGROUND Epilactose, a potential prebiotics, was derived from lactose through enzymatic catalysis. However, production and purification of epilactose are currently difficult due to powerless enzymes and inefficient downstream processing steps. RESULTS The encoding gene of cellobiose 2‐epimerase (CE) from Caldicellulosiruptor sp. Rt8.B8 was cloned and expressed in Escherichia coli BL21(DE3). The enzyme was purified and it was suitable for industrial production of epilactose from lactose without by‐products, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…These results are in accordance with the ones reported by Chen and collaborators that performed a 12 h reaction using 25 U/mL of β-galactosidase from Bifidobacterium bifidum and achieved almost a complete elimination of lactose while 94% of the epilactose was recovered from the reaction mixture [7]. Recently, a screening of β-galactosidase enzymes that could be suitable for epilactose purification showed that the most promising enzyme was the one from Bacillus stearothermophilus [17]. The use of this enzyme resulted in the recovery of 98.5% of the epilactose, while 87.6% of the lactose was hydrolyzed.…”
Section: Optimization Of Lactose Hydrolysis By β-Galactosidase From A...supporting
confidence: 91%
See 2 more Smart Citations
“…These results are in accordance with the ones reported by Chen and collaborators that performed a 12 h reaction using 25 U/mL of β-galactosidase from Bifidobacterium bifidum and achieved almost a complete elimination of lactose while 94% of the epilactose was recovered from the reaction mixture [7]. Recently, a screening of β-galactosidase enzymes that could be suitable for epilactose purification showed that the most promising enzyme was the one from Bacillus stearothermophilus [17]. The use of this enzyme resulted in the recovery of 98.5% of the epilactose, while 87.6% of the lactose was hydrolyzed.…”
Section: Optimization Of Lactose Hydrolysis By β-Galactosidase From A...supporting
confidence: 91%
“…To obtain purer epilactose for food applications as potential prebiotic ingredient, the remaining lactose (73.8 ± 0.5% of the mixture) needs to be removed. As the compounds are isomers, its separation is a complex procedure, and the lactose hydrolysis seems to be the most efficient method to eliminate this sugar [7,17]. However, due to the high similarity of the two structures, both lactose and epilactose can be substrates for microbial enzymes, thus limiting the selection of the most suitable catalyst.…”
Section: Selective Hydrolysis Of Lactosementioning
confidence: 99%
See 1 more Smart Citation